Perspectives on Fractional Reserve Banking and Money Creation/Productio - Mejd Aures Benlala (Perspectives of Law and Public Administration, 2023)
Today’s financial and banking systems are built on fractional reserve banking. This article sheds light on the role of commercial banks with regards to money creation/production under this system of fractional reserve banking. After exploring the nature of the process of money creation/production, the research paper diligently scrutinizes this process through the lenses of legal and religious moral precepts and ethic. The article concludes, with solid supporting arguments, that money creation/production under fractional reserve banking is immoral, ethically wrong and harmful at both individual and societal levels, with numerous legal and religious violations at its core.